Stroke networks and telemedicine: An Italian national survey - Laura Bernetti; Graziamaria Nuzzaco; Francesco Muscia; Alessio Gamboni; Marialuisa Zedde; Paolo Eusebi; Mauro Zampolini; Francesco Corea (MDPI AG, 2018)
Stroke is the leading cause of disability and death. Nowadays, clinical benefits of stroke units and thrombolysis in ischemic stroke are evidence-based. Also the benefit of endovascular treatment for acute ischemic stroke has been established. Telemedicine has been used to improve access to care by allowing a neurologist at a remote location to interact with the patient and their family members. Prior studies have shown that the use of telemedicine for acute ischemic stroke is not only safe and effective, but it also increases the utilization of tPA, improving patient outcomes. This study aimed to investigate the diffusion of telemedicine in Italian stroke networks with an online questionnaire to assess: type of stroke care setting, Volume of thrombolysis- thrombectomy/year, access to stroke care between different hospitals, the presence of imaging sharing protocols within the network or patients dispatchment screening; type of network solutions. We have interviewed 24 Italian neurologists, working in large urban areas, from north southward, including Italian islands. In particular, these neurologists represented 14 different regions and 20 countries. A majority of neurologists replying to the survey (47.83%) worked in large general hospitals or smaller general hospitals (26%) and a smaller number of physicians (17.3%) were committed in University Hospital or (8.7%) independent foundation hospitals. The 60.87% of stroke networks involved in the survey had a low thrombolysis/year volume while the 30.43% had a thrombolysis/year volume above 100. According to the survey a local stroke network was established in 87.50% of cases. In the 45.83% of cases, the hospitals care is not homogeneous within the network. A network for the consultation of neuroimaging between hospitals is available in 33.33% of cases. Whitin those describing an active network for Teleconsult the 57.14% used personal devices, while only the 25 % use professional teleconference system, and in 25% of cases used medical devices. Our findings demonstrated a relevant diffusion of Teleconsult in Italian stroke networks. The systems adopted are mostly individual solutions not integrated in protocolled pathways. These findings may encourage a systematization of Telemedicine medical curricula to increase larger access to neurological consults.